(untitled) - Brache, Alan P. (New York, 2006)
If you see a gap in their organization's ability to translate vision into practice, Implementation is written for you--a guide to action-oriented management that directly reflects your corporate vision. Management experts Alan Brache and Sam Bodley-Scott draw from their decades of experience, giving you the tools to bring organizational strategy to life in day-to-day operations. Using the exclusive Kepner-Tregoe methodology, explain each of the seven essential skills of strategy implementation, providing the tactics and diagnostics needed for success.
Keywords: Organizational effectiveness,Organizational change,Management,Hiệu quả tổ chức,Sự thay đổi tổ chức,Quản lý